Pengembangan Bahan Ajar Fikih Haid Berbasis Animasi Untuk Kelas VI MDTA Miftahul Ulum Nyalabu Daya Pamekasan - Toha, Toha; Sa`diyah, Halimatus; Ihsan, Muhammad; Hariri, Moh. (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Initial observations of teaching Islamic menstrual law (fikih haid) to 6th grade students at MDTA Miftahul Ulum Nyalabu Daya Pamekasan revealed challenges in understanding set theory concepts. Conventional teaching methods without the use of learning aids resulted in minimal student engagement in the learning process. This research aims to develop animated teaching materials for Islamic menstrual law to enhance students' understanding of set theory concepts. Evaluating the effectiveness of animated teaching materials is also a key objective of this study. The research adopts a Research and Development (R&D) approach using the Hannafin and Peck model, encompassing needs analysis, design, and implementation of teaching materials. Validation is conducted through questionnaires administered to three validators to assess the quality of teaching materials in terms of language, content, and audio-visual aspects. Small-scale and large-scale trials are conducted at MDTA Miftahul Ulum Nyalabu Daya Pamekasan.